2021
DOI: 10.1007/s11661-021-06286-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Working and Long-Term Heating in Air on the Stress Corrosion Cracking Growth Rate in Commercial TT Alloy 690 Exposed to Simulated PWR Primary Water

Abstract: The authors have previously reported that the number of cavities at or near grain boundary (GB) carbides in commercial thermally treated (TT) Alloy 690 increases with increasing cold work reduction ratio and with heating temperature in air. In the present work after very long-term heating in air, the number of cavities at or near GB carbides in cold worked commercial TT Alloy 690 was observed to saturate, and the shape and size of the cavities changed. The shape and size of cavities and cracks were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…As a result, intergranular carbides, despite their widely reported beneficial effects on the IGSCC of Alloy 600 [13,52] , could indirectly accelerate the formation of cavities in Alloy 690, contributing to the weakening of the GBs. Similar results were also reported by Kuang et al [40] and Yonezawa et al [53] .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As a result, intergranular carbides, despite their widely reported beneficial effects on the IGSCC of Alloy 600 [13,52] , could indirectly accelerate the formation of cavities in Alloy 690, contributing to the weakening of the GBs. Similar results were also reported by Kuang et al [40] and Yonezawa et al [53] .…”
Section: Discussionsupporting
confidence: 91%
“…In other words, it is necessary to show not only that the temperature dependency of crack growth rate and creep cavity formation are similar, but also that cavity formation and deformation have the same stress dependencies. However, the stress dependency was neither observed in three-point bent beam IGSCC tests nor in reserve U-bend specimen IGSCC tests [53] . Hence, Yonezawa et al [53] suggested that the creep damage might be not the mechanism of IGSCC of CW Alloy 690.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations